2019
DOI: 10.3390/universe5050108
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Blazar OJ 287 and Its Massive Binary Black Hole Central Engine

Abstract: The bright blazar OJ 287 is the best-known candidate for hosting a nanohertz gravitational wave (GW) emitting supermassive binary black hole (SMBBH) in the present observable universe. The binary black hole (BBH) central engine model, proposed by Lehto and Valtonen in 1996, was influenced by the two distinct periodicities inferred from the optical light curve of OJ 287. The current improved model employs an accurate general relativistic description to track the trajectory of the secondary black hole (BH) which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 66 publications
(124 reference statements)
2
60
0
1
Order By: Relevance
“…From SMBHB candidates separated well below the resolution limits of radio interferometers, an extensively studied example is the blazar OJ 287. Its quasi-periodic optical light curve shows double peaks about every 12 yr (Sillanpaa et al, 1988); see also the recent review by Dey et al (2019). These variations have been explained in the context of a number of different binary SMBH scenarios.…”
Section: Radio Imaging Searches For Smbhbs With the Vlbimentioning
confidence: 87%
See 2 more Smart Citations
“…From SMBHB candidates separated well below the resolution limits of radio interferometers, an extensively studied example is the blazar OJ 287. Its quasi-periodic optical light curve shows double peaks about every 12 yr (Sillanpaa et al, 1988); see also the recent review by Dey et al (2019). These variations have been explained in the context of a number of different binary SMBH scenarios.…”
Section: Radio Imaging Searches For Smbhbs With the Vlbimentioning
confidence: 87%
“…The complex VLBI jet of OJ 287 has been described with a helical model (Valtonen and Pihajoki, 2013) in a way that is consistent with the binary orbital motion. Most recently, Britzen et al (2018) presented an extensive study of the jet emission of OJ 287 at cm wavelengths, combining VLBI and single-dish radio data, and found that precession of an accretion disk around a single SMBH can explain the observed periodic behaviour of the jet morphology and radio flux density changes (but not the optical long-term lightcurve and polarimetry; Dey et al 2019). A binary is still likely needed in that model for explaining the disk precession itself.…”
Section: Radio Imaging Searches For Smbhbs With the Vlbimentioning
confidence: 99%
See 1 more Smart Citation
“…The binary black hole (BBH) central engine description for the bright blazar OJ287 provides the most promising scenario for the existence of a nano-Hz GW emitting massive BH binary (Dey et al 2019). The model naturally explains the observed double-peaked high brightness flares (outbursts) from OJ287 and predicts the arrival time of future outbursts.…”
Section: Introductionmentioning
confidence: 99%
“…Our aim is revisiting the issue of analytically calculating the 2PN pericentre precession by straightforwardly computing it perturbatively with the widely known method of variation of the orbital elements (Tisserand 1889;Plummer 1960;Brouwer & Clemence 1961;Danby 1962;Soffel 1989;Brumberg 1991;Murray & Dermott 2000;Bertotti, Farinella & Vokrouhlický 2003;Roy 2005;Kopeikin, Efroimsky & Kaplan 2011;Poisson & Will 2014;Soffel & Han 2019) in order to provide quickly understandable formulas, ready to be used in practical calculations in view of possible measurements in a not so far future, more likely in binary pulsars than in our Solar system, or to better model the dynamics of peculiar systems like, e.g., tight extrasolar planetary systems or the BL Lac object OJ 287 (Dey et al 2018(Dey et al , 2019. A similar strategy was adopted in Kopeikin & Potapov (1994).…”
Section: Introductionmentioning
confidence: 99%